Social welfare versus inequality aversion in an incomplete contract experiment - Marco Faravelli; Oliver Kirchkamp; Helmut Rainer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We explore experimentally how power asymmetries between partners affect relationship-specific investments. We find that on average players' investments are larger than equilibrium investments. In contrast to social dilemma experiments, in our experiment preferences for social welfare and those for equality call for different actions. Surprisingly, even disadvantaged players care more for social welfare and less for equality. As a result social welfare increases but so does inequality. We then study conditions under which power-advantaged players give up power. Power-sharing can be successful in the experiment, even when it is not in a selfish world.
Keywords: C91; D23; D86; 330; Experiments; incomplete contracts; relationship-specific investment; allocation of Power; social preferences; Soziale Beziehungen; Soziale Ungleichheit; Gerechtigkeit; Soziale Wohlfahrtsfunktion; Unvollständiger Vertrag; Macht; Test